CODE-SWITCHING IN EFL CLASSROOM: IS IT GOOD OR BAD? - N. Nurhamidah; Endang Fauziati; Slamet Supriyadi (Journal of English Education, 2018)
Code-switching has been an evolving topic since the bilingualism blooming in linguistics milieu. However, practitioners or experts have contrastive views regarding its use in classroom setting. While the proponents believe that the presence of code-switching in one side is considered as an asset to teach language, the opponents see it is as merely an obstacle to achieve learning goal that is to acquire target language. Code-switching serves many functions for both teacher and students yet it is still employed. Despite the pro and cons of the code-switching, this research aims to show the perspective of both teacher and students towards code-switching and functions it serve in EFL classroom setting. This research used qualitative descriptive approach and the data were taken from the informants of English department in one of university in Surakarta to explore whether the use of code-switching in EFL classroom was seen as beneficial tool. It begins by the general view of EFL use in everyday classroom. This current study found that code-switching was preserved as benefits as it served some functions for teacher to convey material and for students to received material and communicate in classroom.